2017
DOI: 10.1002/adhm.201600549
|View full text |Cite
|
Sign up to set email alerts
|

Full‐Thickness Heart Repair with an Engineered Multilayered Myocardial Patch in Rat Model

Abstract: Structural cardiac defects, such as Tetralogy of Fallot, often requires surgical placement of a patch to expand the right ventricular outflow tract (RVOT) in an area normally consisting of contractile myocardial tissue. Current cardiac patch materials are biologically inert and will not grow with a pediatric patient, often requiring reoperations. In this study, novel multi-layered scaffolds with a polycaprolactone core, a chitosan-based scaffold, and either gelatin or decellularized porcine heart matrix were i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
27
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 31 publications
(28 citation statements)
references
References 22 publications
1
27
0
Order By: Relevance
“…The patch had ideal potential for direct use as a thick patch for myocardial replacement. Pok et al modified the patch by adding a polycaprolactone (PCL) core, and tested the therapeutic potential of the patch in a rat infarction model . Pourfarhangi et al evaluated the optimized ratio of cECM and chitosan for improving CPC function, and determined that higher cECM composition in composite patches improved CPC viability .…”
Section: Soluble Decmmentioning
confidence: 99%
See 1 more Smart Citation
“…The patch had ideal potential for direct use as a thick patch for myocardial replacement. Pok et al modified the patch by adding a polycaprolactone (PCL) core, and tested the therapeutic potential of the patch in a rat infarction model . Pourfarhangi et al evaluated the optimized ratio of cECM and chitosan for improving CPC function, and determined that higher cECM composition in composite patches improved CPC viability .…”
Section: Soluble Decmmentioning
confidence: 99%
“…In surgical treatments for Tetralogy of Fallot, patches most often composed of nondegradable, bioinert materials such as nylon or noncardiac specific materials such as SIS are placed across the right ventricular outflow tract (RVOT). Pok et al generated a bioactive, degradable full‐thickness cardiac patch composed cECM/chitosan and PCL layers for use as a RVOT patch and compared the system to patches composed of gelatin/chitosan/PCL and pure bovine pericardium . By week 8, both gelatin and cECM patches showed similar decreases in PCL thickness.…”
Section: In Vivo Evaluation Of Decm Therapies For Cardiovascular Tissmentioning
confidence: 99%
“…In addition, the ABMs should be able to sense a wider frequency range of 100 Hz to 8 kHz, and be sensitive enough to detect sound with a minimum of ≈40 dB SPL . Packaging for chemical and electrical stability and subsequent verification of long‐term biocompatibility are also essential . In addition to optimizing the ABM itself, research on the whole CI system should be performed for the development of next‐generation devices.…”
Section: Future Perspectives For Next‐generation Cis Using Abmsmentioning
confidence: 99%
“…Previous studies found that ECM can be harvested from tissues such as cartilage, skeletal muscle, tendons, adipose tissue, vessels, lung, liver, intestine (17,21,22) and bovine ureter (23), and may be applied as biological scaffolds with beneficial results. Previous studies in which porcine heart matrix was used for construction of tissue engineered heart patches demonstrated that porcine ECM could support cardiomyocytes, improved heart function and was capable of heart defect repair (24,25). However, ECM is frequently derived from non-cardiac or heart tissue of other species.…”
Section: Introductionmentioning
confidence: 99%